TRIBUNAL ADJUDICATION IN INDIA: NEED, GROWTH AND REFORMS NEEDED - Kumar, Anjay; Pandey, Ujjaval (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In a developing country like India, with the infrastructural development in various sectors also led to rise in dispute among the concerns. These disputes affect the citizens, requires a special judicial body to deal with them on the basis of technicalities involved. To deal with such problems and without affecting the powers and to keep away constitutional courts from such disputes related to a specific sector, opened the doors for entry of tribunals. These tribunals are form formed by a statute passed by the parliament or legislature. The tribunals mainly by pass the jurisdiction of District Courts and, in specific matters and statutes of High Courts except their constitutional powers to deal matters. These tribunals contain the one of the main functions of judiciary, bindingness of its decisions which also plays an important role in recognition. The adjudication through this quasi-judicial wing grown with rapid speed as it not only covers all technical and sectoral aspect but also free from rigid or lengthy procedure of the normal courts. This study tries to deal with the need of tribunals due to their nature of working, reasons of growth of tribunals along with the future reforms needed in tribunal adjudication.